Estados Nacionales Y VÃctimas Sacrificiales: Consideraciones Sobre El Genocidio Maya-Ixil En Guatemala - MÃ©ndez, Eliana CÃ¡rdenas (European Scientific Journal, ESJ, 2018)
"Tierra Arrasada" (Scorched Earth) was a military program applied in Guatemala by former President JosÃ© EfraÃn RÃos Montt, against Mayan communities accused of collaborating with the guerrilla force, and had the aggravating elements of a genocidal campaign. The guiding question of this essay is: â€œWhat is the reason for the genocides against ancestral peoples?â€, and has the following starting hypothesis: the modern nation states, as "imagined communities", contain an inherent â€œbio-racialâ€ component which gives sense and structure to the power instrumentation. Racism is recognized as a root element in Guatemalan history and, together with socioeconomic and political factors, has led to the genocide of Ixil people. Following RenÃ© Girard, this paper proposes that Ixils were "sacrificial victims" in the contest for power between the Guatemalan State and the EjÃ©rcito Guerrillero de los Pobres (EGP) in order to sustain the hegemonic power with low political and military costs. Methodologically it is the results of field studies among communities of former Guatemalan refugees in Quintana Roo, Mexico, as well as historical and discourse analysis. The aim of this paper is to present the semantic potential of a theory of mimetics for the study of genocides in modern states.